Detection of AtRKD4 Protein During Induction of Somatic Embryogenesis in Dendrobium lineale Rolfe Transgenic Orchids Carrying 35S::GR::AtRKD4 - Gde Cahyadi Wirajagat; Ni Luh Putu Kayika Febryanti; Fitriana Puspitasari; Dika Sundari; Jose Gutierrez-Marcos; Endang Semiarti (Universitas Gadjah Mada, 2021)
Dendrobium lineale is an Indonesian native orchid from the Spatulata section in Orchidaceae Family. This orchid is important because it is usually used as a parental plant in orchid breeding and is predicted to have a potential phytochemistry compound. In addition, in their natural habitat, this orchid is threatened due to forest exploitation and natural disaster. Therefore the precision mass propagation techniques for this orchid need to be conducted. Biotechnological approaches through inserting embryo gene such as AtRKD4 from Arabidopsis thaliana has already been successfully conducted. This study aims to check the integration stability of T-DNA harboring 35S::GR::AtRKD4 from ten selection transformants and to detect the existence of AtRKD4 protein after induction by Dexamethasone and/ Thidiazuron. The result showed that T-DNA were stably integrated into the genome of D. lineale transformants and the AtRKD4 protein with a molecular weight of 28.53 kDa was detected in D. lineale transformant plants after being induced by 15 µM DEX and 3 mgL-1 TDZ for 5 days.